2015
DOI: 10.1111/cobi.12549
|View full text |Cite
|
Sign up to set email alerts
|

Future habitat loss and extinctions driven by land‐use change in biodiversity hotspots under four scenarios of climate‐change mitigation

Abstract: Numerous species have been pushed into extinction as an increasing portion of Earth's land surface has been appropriated for human enterprise. In the future, global biodiversity will be affected by both climate change and land-use change, the latter of which is currently the primary driver of species extinctions. How societies address climate change will critically affect biodiversity because climate-change mitigation policies will reduce direct climate-change impacts; however, these policies will influence la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 45 publications
1
131
0
8
Order By: Relevance
“…All future scenarios show an increase in secondary vegetation area at the cost of the natural habitat primarily to meet the increasing wood demand [9]. We found that this leads to substantial biodiversity loss in all six scenarios ( Table 2), indicating that, regardless of climate mitigation, sustainable forest management will be critical for future biodiversity conservation.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…All future scenarios show an increase in secondary vegetation area at the cost of the natural habitat primarily to meet the increasing wood demand [9]. We found that this leads to substantial biodiversity loss in all six scenarios ( Table 2), indicating that, regardless of climate mitigation, sustainable forest management will be critical for future biodiversity conservation.…”
Section: Discussionmentioning
confidence: 90%
“…The scope of our study mirrors that of Jantz et al [9], who also quantified the potential extinctions in biodiversity hotspots under future land use change scenarios, but did not model the climate change effects. However, climate change can degrade currently suitable habitats, can shift suitable habitats to areas that cannot be reached, and can produce unsuitable or unavailable climate envelopes, all which can threaten species directly, driving them towards extinction [47,48], and several studies have demonstrated that climate-change will exacerbate the impact of habitat loss on species [49][50][51][52].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, it is evident that biodiversity can be in critical conflict with demands for land resources such as food or timber (Behrman et al, 2015;Murphy and Romanuk, 2014). LUC has been the most critical driver of recent species loss (Jantz et al, 2015;Newbold et al, 2014). This has led to substantial concerns that land requirements for bioenergy crops would be competing with conservation areas directly or by leakage.…”
Section: Potential Impacts On Biodiversitymentioning
confidence: 99%